2007
DOI: 10.1097/id.0b013e3180500a84
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Histological Evaluation of Immediate-Loaded Posterior Implants in Nonhuman Primates

Abstract: Immediate-loaded implants in the nonhuman primates often have a higher bone-implant contact percentage at 90 days than unloaded implants. The bone remodeling is different for loaded implant-bone interfaces than for unloaded conditions. However, 1 immediate-loaded implant failed, and 2 implants had lower bone-implant contact percentage than controls. Therefore, although there are benefits of immediate loading, there appear to also be some risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…When implants are loaded for 12 weeks, the presence of peri‐implant osteoid tissue and the BIC increase significantly. Another study on primates confirmed that immediately loaded implants show a greater BIC (62.4%) compared with that of not loaded implants (56.3%) 3 …”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…When implants are loaded for 12 weeks, the presence of peri‐implant osteoid tissue and the BIC increase significantly. Another study on primates confirmed that immediately loaded implants show a greater BIC (62.4%) compared with that of not loaded implants (56.3%) 3 …”
Section: Discussionmentioning
confidence: 90%
“…Moreover, occlusal loading of the implants can be allowed to assure a certain degree of masticatory function in accurately evaluated and monitored patients. Not to be disregarded is the observation that early function may have a favorable effect on bone formation and mineralization, 2 determining a higher degree of bone–implant contact 3 …”
Section: Introductionmentioning
confidence: 99%
“…When we compare this 2‐week pre‐loading period with our 3‐month pre‐loading stage, those implants might be described as ‘early loaded’. Additionally, Suzuki et al (2007) state that the bone remodelling is different for loaded implant–bone interfaces than for unloaded conditions. They report that immediately loaded implants have a higher bone–implant contact percentage at 3 months than unloaded implants.…”
Section: Discussionmentioning
confidence: 99%
“…This primate was part of a previously published study by Suzuki et al, 7 where large bilateral mandibular ridge osseous defects were created secondary to bone block biopsies of immediately loaded BioHorizons (Birmingham, AL) endosseous dental implants ( Fig. 1).…”
Section: Clinical Proceduresmentioning
confidence: 99%